Dipeptidyl Peptidase IV as a Muscle Myokine - Kluess, Heidi A. (Frontiers in Physiology, 2020)
Dipeptidyl peptidase IV (DPP-IV) is a unique serine protease that exists in a membrane bound state and in a soluble state in most tissues in the body. DPP-IV has multiple targets including cytokines, neuropeptides, and incretin hormones, and plays an important role in health and disease. Recent work suggests that skeletal muscle releases DPP-IV as a myokine and participates in control of muscle blood flow. However, few of the functions of DPP-IV as a myokine have been investigated to date and there is a poor understanding about what causes DPP-IV to be released from muscle.